The athlete`s heart: Towards tailored clinical decision-making on athlete screening - Panhuyzen-Goedkoop, N.M. (University of Amsterdam, 2024)
Over the years, the spectrum of competitive and recreational athletes has significantly expanded, including various age groups, diverse sex distribution and ethnic origin. Consequently, while the statements regarding athlete screening outcomes and cardiac remodeling may be qualitatively correct, there is a need for new data and evidence on cardiac adaptation that accurately represent the changing spectrum of sports participants. New diagnostic modalities may be helpful in discriminating adaptation from pathology, particularly using CMR.